Gender Differences in German Wage Mobility - Bodo Aretz (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
This paper analyzes the evolution of wage inequality and wage mobility separately for men and women in West and East Germany over the last four decades. Using a large administrative data set which covers the years 1975 to 2008, I find that wage inequality increased and wage mobility decreased for male and female workers in East and West Germany. Women faced a higher level of wage inequality and a lower level of wage mobility than men in both parts of the country throughout the entire observation period. The mobility decline was sharper in East Germany so that the level of wage mobility has fallen below that of West Germany over time. Looking at long-term mobility, a slowly closing gap between men and women is observed.
Keywords: J31; D63; D00; 330